Prevalência e características das mulheres com aborto provocado. Favela México 70, São Vicente-SP - Santos, Tássia Ferreira [UNIFESP] (2010)
The metropolitan area of Santos, despite being one of the most developed and urbanized of the São Paulo state, is among the six regions with the lowest indicators of education and longevity, having a significant social inequality expressed in the spatial segregation of the impoverished population. This situation interferes with the community reproductive profile. The objective of this research was to estimate the prevalence of women with caused abortion, residents in the community of Mexico 70, according to demographic characteristics. This study is cross-sectional, retrospective, resulted from a random sample of women ranged from 15 to 49 years. Data were collected through questionnaires. Was considered as the dependent variable classification of women on abortion: age, paid activity, income, level of education, marital status, contraceptive use and beliefs about abortion. For the analysis of regression models were used log-binomial. among the total women interviewed (n=860), 79,53% (n=684) are women with no history of induced abortion; considering all women, the prevalence rate of those who had performed the abortion compared to those who hasn‟t is 6,20 times greater (p≤0,0001) among women who always accept abortion; 2,92 times greater (p=0,0046) among those with two or more children born alive; 1,69 times greater (p=0,0461) among those who receive income ≤ 1SM(Rdollar 484,97); 1,04 times higher (p=0,0375) for each additional year of life for women. Among the 860 women, 85% (n=735) reported have had any pregnancy, and among them, the prevalence of women with induced abortion was 6,9% (n = 51). The prevalence rate of have done the abortion compared to no abortion is 12,22 times greater (p=0,0002), among those who do not have any child born alive; 5,73 times greater (p≤0,0001) between the ones who accept this practice; 5,18 times greater (p=0,0162) among those with six or more live births of children; 4,52 times higher (p=0,0108) among those with two to five children born alive; 1,76 times greater (p=0,0345) among those who receive income (≤R{dollar}484,97); 1,04 times higher (p=0,0216) for each additional year of life for women. Finally, the profile of women who have abortions was determined, and the same is: young, single, with children, level of education and not working out.